How the Pacific Oyster Responds to Ocean Acidification: Development and Application of a Meta-Analysis Based Adverse Outcome Pathway - Ducker, James; Falkenberg, Laura J. (Frontiers in Marine Science, 2020)
Biological fitness relies on processes acting at various levels of organization, all of which can be modified by environmental change. Application of synthesis frameworks, such as the Adverse Outcome Pathway (AOP), can enhance our understanding of the responses to stressors identified in studies at each level, as well as the links among them. However, the use of such frameworks is often limited by a lack of data. In order to identify contexts with sufficient understanding to apply the AOP framework, we conducted a meta-analysis of studies considering ocean acidification effects on calcifying mollusks. Our meta-analysis identified that most studies considered the adult life history stage, bivalve taxonomic group, individual-level changes, as well as growth and metabolism related responses. Given the characteristics of published literature, we constructed an AOP for the effects of ocean acidification on calcification in an adult bivalve, specifically the Pacific oyster (Magallana gigas). By structuring results within the AOP framework we identify that, at present, the supported pathways by which ocean acidification affects oyster calcification are via the downregulation of cavortin and arginine kinase transcription. Such changes at the molecular level can prompt changes in cellular and organ responses, including altered enzyme activities, lipid peroxidation, and regulation of acid-base status, which have impacts on organism level metabolic rate and, therefore, calcification. Altered calcification may then impact organism mortality and population sizes. We propose that where developed and incorporated in future studies, the AOP framework could be used to investigate sources of complexity including varying susceptibility within and among species, feedback mechanisms, exposure duration and magnitude, and species interactions. Such applications of the AOP framework will allow more effective reflections of the consequences of environmental change, such as ocean acidification, on all levels of biological organization.